The road to Roswell : a novel - Willis, Connie (Del Rey, 2023)
"When level-headed Francie arrives in Roswell, New Mexico, for her college roommate's UFO-themed wedding-complete with a true-believer bridegroom-she can't help but roll her eyes at all the wide-eyed talk of aliens, which obviously don't exist. Imagine her surprise, then, when she is abducted by one"--